Microbial Load of Chicken Shawerma and the Handlers’ Compliance with Food Safety Practices in Jordan - Taha, Hana; Nasraween, Moath; Khader, Yousef; Al Omari, Lujain; Al Nsour, Mohannad; Al Shdaifat, Amjad; Berggren, Vanja (Arab Journal of Nutrition and Exercise (AJNE), 2022)
Background: Shawerma is a popular traditional food in the Eastern Mediterranean region. Aim: The aim of this study was to assess the shawerma handlers’ compliance with food safety practices and determine the microbial load and pathogenic organisms in the ready-to-eat chicken shawerma sandwiches in the restaurants of Amman, Jordan. Methods: This cross-sectional study used mixed methods including observational checklists to determine the compliance of food safety practices by 120 chicken shawerma handlers from 40 randomly selected restaurants in Amman. Additionally, pathogenic microorganisms were assessed by laboratory analysis in the ready-to-eat chicken shawerma sandwiches. Results: Only 2.5% and 10% complied, respectively, with separating knives and boards used for chicken from the ones used for vegetables. The compliance for maintaining proper temperatures for freezers and chillers were only 62% and 67%, respectively. As for hand-washing techniques and using disposable drying papers, the adherence was 5% and 7.5%, respectively. Laboratory analysis showed that 27.5% of the ready-to-eat shawerma had unacceptable levels of microorganisms. Conclusion: Our findings showed poor compliance of food safety practices in chicken shawerma restaurants of Amman. There is a need for capacity building and periodic evaluations of food handlers’ knowledge and practices within a comprehensive food safety program, carried out by qualified trainers. Keywords: chicken shawerma, food safety, Jordan